Sketching T cell atlases in the single‐cell era: challenges and recommendations - Bojović, Itana; Sousa, António GG.; Junttila, Sini; Elo, Laura L. (Wiley, 2025)
Recent advances in single-cell technologies have enabled the creation of comprehensive cell atlases, reference maps of various cell types within organisms. Here we specifically focus on T cell atlases, which offer a detailed catalog of the adaptive immune system at single-cell resolution. As such, they capture cellular diversity, functional states, and spatial dynamics across tissues, developmental stages, and disease conditions. Given the central role of T cells in orchestrating immune responses, their dysregulation underpins autoimmune disorders, cancer progression and failed immunotherapies. Therefore, a unified T cell atlas is critical for decoding such disease mechanisms, identifying therapeutic targets, and advancing personalized treatments. In this article, we explore the latest advances in T cell atlases, describing breakthroughs in multi-omics technologies, spatial profiling and computational frameworks that resolve transcriptional, epigenetic and proteomic heterogeneity. We also address persistent challenges and highlight strategies to address these gaps. Finally, we discuss emerging frontiers set to reshape our understanding of T cell dynamics in both health and diseases. Together, these insights underscore the transformative potential of T cell atlases in reconstructing precision immunology and accelerating therapeutic innovation.